Peran Guru dan Orang Tua dalam Menanamkan Karakter Mandiri pada Anak Usia Dini di RA. An Nur Medan - Misnan, Misnan; Sari, Nurmaya; Siagian, Rosimah; Nazifah, Nurun (AUD Cendekia: Journal of Islamic Early Childhood Education, 2021)
This study aims to analyze (1) the role of parents and teachers in instilling independent characters in children, (2) the obstacles faced in instilling independent characters in children. This research was conducted at RA An Nur Medan, with the research method used was qualitative with a descriptive study approach. The research participants were teachers, parents, students, and school principals. Data analysis used the Miles and Huberman technique, namely data reduction, data display, and drawing conclusions. The results showed that (1) the role of parents in instilling independent characters can be seen from parents who are invited to participate in instilling various kinds of good characters in students, including independent characters. This is even more so during the distance learning period that has been affected by the Covid 19 pandemic. The collaboration referred to in this case is not limited to supervising student activities while at home, but more than that. In the process of internalizing the independent character, parents are invited to participate as non-formal teachers who familiarize Ana to be able to independently carry out various activities, especially activities related to children's affairs and individuals. (2) the teacher's role in instilling independent character can be seen from several steps that the teacher teaches students, namely: character selection, practice, habituation, and example. (3) Obstacles faced by teachers and parents in instilling independent character in early childhood at RA An Nur Medan are lack of parental enthusiasm, lack of supervision, psychological disorders of children